A key ABA biosynthetic gene OsNCED3 is a positive regulator in resistance to Nilaparvata lugens in Oryza sativa - Li, Jitong; Liu, Hao; Lv, Xinyi; Wang, Wenjuan; Liang, Xinyan; Chen, Lin; Wang, Yiping; Liu, Jinglan (Frontiers in Plant Science, 2024)
The brown planthopper (BPH, Nilaparvata lugens) is one of the most important pests of rice in China and causes damage by ingesting phloem sap. OsNCED3 is a key gene in abscisic acid (ABA) synthesis and functions in drought resistance. Interestingly, it is not known if OsNCED3 overexpression can increase resistance to BPH or whether drought resistance is correlated with pest resistance. In this study, the role of OsNCED3 in BPH resistance was evaluated in rice by conducting physiological and biochemical assays, monitoring changes in hormones, and evaluating expression of defense genes. Our results show that the defense gene OsNCED3 is induced by BPH feeding and correlates with improved plant resistance to BPH in 48 h. Our findings also support a role for several plant hormones as defense compounds in the rice-BPH interaction. Although the control of BPH is still based on chemical methods, the results of this study indicate that modulation of endogenous genes in rice may also be utilized to lessen yield loss, which would be beneficial for the environment due to the reduced use of chemicals.